The Effect of Financial Ratios toward Stock Returns among Indonesian Manufacturing Companies - James Andi Wijaya (iBuss Management, 2015)
Indonesian Composite Index (ICI) is the top gainer among major Asia-Pacific indices during 2008-2013. Inside the composite index, manufacturing index showed a stronger growth compared to the composite index. Thus, this study analyzes the influence of financial ratios toward stock returns in Indonesian manufacturing companies. The data in this research are obtained using judgmental sampling method consisting of 100 samples from 20 major listed Indonesian manufacturing companies during 2008-2013. Furthermore, the data were analyzed by using multiple linear regression analysis. The results showed that return on assets, debt to equity, dividend yield, earnings yield, and book to market simultaneously have a significant effect on stock returns. Partially, return on assets, dividend yield, earnings yield, and book to market have significant effects on stock returns. However, debt-to-equity ratio does not have partial significant effect on stock returns. Keywords: Financial Ratio, Stock Return, Profitability Ratio, Debt Ratio, Market Ratio.